Self-regulation of Learning and Personality: a Predictive Study in University Students from the Ecuadorian Highlands - Males-Villegas, Ángel (2023)
This research analyzes the psychometric properties, the influence of sociodemographic variables, the level of association and prediction between Zimmerman’s self-regulation model of learning and Zuckerman’s psychobiological model of personality in university students from the Ecuadorian highlands. A total of 394 undergraduate students from the cities of Quito, Ambato and Loja were surveyed by non-probabilistic sampling. Data were analyzed by descriptive statistics, reliability methods, content and construct validation, Spearman’s correlation and multiple linear regression using software and technological tools. The results show: a) reliability and validity of the ISLP and ZKPQ-50cc instruments, b) gender and age influence on personality traits, while study modality influences self-regulation of learning and personality, c) personality traits reveal low and medium relationships with self-regulation of learning and d) personality traits of: activity, aggression-hostility and neuroticism-anxiety influence on self-regulation of learning.